Treatment of neurological injury with thymosin β4 - Morris, Daniel C. (2012)
Neurorestorative therapy targets multiple types of parenchymal cells in the intact tissue of the injured brain tissue to increase neurogenesis, angiogenesis, oligodendrogenesis, and axonal remodeling during recovery from neurological injury. In our laboratory, we tested thymosin β4 (Tβ4) as a neurorestorative agent to treat models of neurological injury. This review discusses our results demonstrating that Tβ4 improves neurological functional outcome in a rat model of embolic stroke, a mouse model of multiple sclerosis, and a rat model of traumatic brain injury. Tβ4 is a pleiotropic peptide exhibiting many actions in several different types of tissues. One mechanism associated with improvement of neurological improvement from Tβ4 treatment is oligodendrogenesis involving the differentiation of oligodendrocyte progenitor cells to mature myelin-secreting oligodendrocytes. Moreover, our preclinical data provide a basis for movement of Tβ4 into clinical trials for treatment of these devastating neurological diseases and injuries.